The acute effect of maximal voluntary isometric contraction pull on start gate performance of snowboard and ski cross athletes. Issue 5 (October 2016) - Haycraft, Jade AZ; Gastin, Paul B; Robertson, Sam
This study investigated whether adding a maximal voluntary isometric contraction to developing snowboard and ski cross athletes' warm-up could reduce start time. A secondary aim was to assess the appropriateness of start performance as a talent identification tool for junior athletes by determining whether differences in time could be explained by participant age and anthropometry. Twenty sub-elite athletes (male: n = 11, female: n = 9, age: 15.0 ± 1.4 years) participated. No differences were found for start time (7.5 m) between maximal voluntary isometric contraction and standardised (no-maximal voluntary isometric contraction) warm-up or gender (maximal voluntary isometric contraction; males: 1.36 ± 0.07 s, females: 1.41 ± 0.03 s, no-maximal voluntary isometric contraction; males: 1.35 ± 0.01 s, females: 1.38 ± 0.10 s, P  > 0.05). A strong relationship between body mass and start time to 7.5 m ( r  = −0.78, r 2  = 0.61, P  < 0.05) was observed. Use of maximal voluntary isometric contraction-based warm-ups with developing snowboard cross and ski cross athletes may not be beneficial to improving performance.